2018
DOI: 10.3847/1538-4357/aaa3e5
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Photometric Reverberation Mapping Analysis on SDSS-RM and Stripe 82 Quasars

Abstract: We modified the broadband photometric reverberation mapping (PRM) code, JAVELIN, and tested the availability to get broad line region (BLR) time delays that are consistent with the spectroscopic reverberation mapping (SRM) project SDSS-RM. The broadband light curves of SDSS-RM quasars produced by convolution with the system transmission curves were used in the test. We found that under similar sampling conditions (evenly and frequently sampled), the key factor determining whether the broadband PRM code can yie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Also, the emission lines are often too narrow in comparison to the width of the broad-band filter, and the contrast between the continuum and the line is difficult to measure. Zhang et al (2018) show that the line flux to continuum flux ratio should be 6 % or larger for the broad-band RM to be effective. To overcome these problems, Jiang et al (2016) used a combination of broad-band and medium-band with the band widths of 180-264 Å which are several times narrower than typical broad-band filter widths.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Also, the emission lines are often too narrow in comparison to the width of the broad-band filter, and the contrast between the continuum and the line is difficult to measure. Zhang et al (2018) show that the line flux to continuum flux ratio should be 6 % or larger for the broad-band RM to be effective. To overcome these problems, Jiang et al (2016) used a combination of broad-band and medium-band with the band widths of 180-264 Å which are several times narrower than typical broad-band filter widths.…”
Section: Introductionmentioning
confidence: 89%
“…To overcome the shortcomings of the spectroscopic RM, purely photometric RM has successfully been performed adopting broad-bands only or a combination of broad-, medium-, and narrow-bands (Haas et al 2011;Pozo Nuñez et al 2012Edri et al 2012;Hernitschek et al 2015;Jiang et al 2016;Zu et al 2016;Zhang et al 2018). Such a technique opens up a possibility of performing the RM of more than thousands of AGNs at once, even using a moderately sized telescopes.…”
Section: Introductionmentioning
confidence: 99%
“…A stochastic process model has been widely used to describe the optical variability of AGN accretion disks (e.g., Kelly et al 2009;MacLeod et al 2010;Zu et al 2013;Rakshit & Stalin 2017;Li & Wang 2018;Zhang et al 2018;Lu et al 2019;Burke et al 2021). Generally, the damped random-walk (DRW) model can provide a successful fit to the long-term variability of AGN accretion disks.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that AGNs variability in the optical band can be well described by the DRW (e.g., Kelly et al 2009;Kozłowski et al 2010;MacLeod et al 2010MacLeod et al , 2011Zu et al 2013;Rakshit & Stalin 2017). The model has been widely used in modeling AGN light curves in reverberation mapping (RM) studies (see Zu et al 2011;Pancoast et al 2011;Grier et al 2012;Li et al 2013;Zhang et al 2018). The limitations of the DRW model in describing AGN variability characteristics will be discussed in Section 4.…”
Section: Sample and Propertiesmentioning
confidence: 99%